A Rapid and Green Method for the Preparation of Solketal Carbonate from Glycerol - Sanjib Kumar Karmee; Sreedhar Gundekari; Louis C. Muller; Ajinkya Hable (Reactions)
Glycerol is a biogenic waste that is generated in both the biodiesel and oleo-chemical industries. The value addition of surplus glycerol is of utmost importance for making these industries economically profitable. In line with this, glycerol is converted into glycerol carbonate, a potential candidate for the industrial production of polymers and biobased non-isocyanate polyurethanes. In addition, glycerol can also be converted into solketal, which is the protected form of glycerol with a primary hydroxyl functional group. In this contribution, we developed a microwave-assisted solvent and catalyst-free method for converting solketal into solketal carbonate. Under conventional heating conditions, the reaction of solketal with dimethyl carbonate resulted in 70% solketal carbonate in 48 h. However, under microwave heating, 90% solketal carbonate was obtained in just 30 min. From the perspective of sustainability and green chemistry, biomass-derived heterogeneous catalysts are gaining importance. Therefore, in this project, several green catalysts, such as molecular sieves (MS, 4Å), Hβ-Zeolite, Montmorillonite K-10 clay, activated carbon from groundnut shell (Arachis hypogaea), biochar prepared from the pyrolysis of sawdust, and silica gel, were successfully used for the carbonyl transfer reaction. The obtained solketal carbonate was thoroughly characterized by 1H NMR, 13C NMR, IR, and MS. The method presented here is facile, clean, and environmentally benign, as it eliminates the use of complicated procedures, toxic solvents, and toxic catalysts.